FORMULASI DAN UJI FISIK GEL HANDSANITIZER EKSTRAK ETANOL DAUN SALAM (Syzygium Polyanthum) DENGAN VARIASI KONSENTRASI CARBOPOL - Jayanti Djarami; Aulia Debby Pelu; Ainun Pamana (Jurnal Kesehatan Amanah, 2021)
The COVID-19 pandemic has made hand sanitizer gel widely used. Hand sanitizer gels generally contain alcohol as an antiseptic to kill bacteria, but long-term use of antiseptics containing alcohol can cause skin irritation. So we need natural alternative materials that have antibacterial power but are friendly to the skin and do not cause irritation. One of theplants that can be used as an antibacterial is a bay leaf (Syzygium polyanthum) because it contains flavonoids that can act as an antiseptic against bacteria. The purpose of this study is to find out the formulation and physical test of the gel hand sanitizer of the ethanol extract of bay leaves (Syzygium polyanthum) with a variety of carbopol concentrations. this study used an experimental design. Three formulations were made with different concentrations of carbopol, namely formula I (carbopol 0.5%), formula II (carbopol 1%), and formula III (carbopol 1.5%). Of the three formulas, physical properties were evaluated which included organoleptic tests, homogeneity tests, and PH tests. The results showed that formula I (carbopol 0.5%), and formula II (carbopol 1%) met the requirements for evaluating the physical properties of the hand sanitizer gel which included organoleptic tests, homogeneity tests, and PH tests. While formula III (carbopol 1.5%) did not meet the physical test, namely the PH test.